Decline in hospitalization risk and health care cost after initiation of depot antipsychotics in the treatment of schizophrenia - Xiaomei Peng; Haya Ascher-Svanum; Douglas Faries et al (Dove Medical Press, 2011)
Xiaomei Peng, Haya Ascher-Svanum, Douglas Faries, Robert R Conley, Kory J SchuhEli Lilly and Company, Indianapolis, IN, USAPurpose: To assess change in hospitalization and cost of care from 6 months pre- to 6 months post-initiation on any depot antipsychotic among schizophrenia patients.Patients and methods: Using a large United States commercial claims and encounters database, patients younger than 65 years diagnosed with schizophrenia were identified. Patients initiated on a depot antipsychotic were studied in a mirror-image design to assess change in hospitalization rates, mean duration hospitalized, and hospitalization cost. McNemar’s test and paired t-tests compared the proportions of patients hospitalized and the mean duration. Paired t-test and bootstrapping methods compared costs.Results: In these patients (n = 147), psychiatric hospitalizations declined from 49.7% pre-initiation to 22.4% post-initiation (P < 0.001), and the mean hospitalized duration for psychiatric purposes numerically declined from 7.3 to 4.7 days (P = 0.05). Total health care costs declined from $11,111 to $7884 (P < 0.05) driven by reduction in costs for psychiatric hospitalizations from $5384 to $2538 (P < 0.05).Conclusion: Initiation of depot antipsychotic therapy appeared to be associated with a decline in hospitalization rates and costs. Current findings suggest that treatment with depot antipsychotics may be a cost-effective option for a subgroup of patients with schizophrenia who are at high risk of nonadherence with their oral antipsychotic medication regimen.Keywords: mirror-image, claims database, treatment outcomes, depot antipsychotics